Qualities of effective teachers - Stronge, James H. (Alexandria, VA : Association for Supervision and Curriculum Development, 2007)
A comprehensive guide that describes the characteristics and skills of effective teachers with advice on developing student achievement, establishing a learning-focused classroom environment, and helping special-needs students.
Prerequisites for effective teaching -- The teacher as a person -- Classroom management and organization -- Planning and organizing for instruction -- Implementing instruction -- Monitoring student progress and potential -- Effective teaching: what does it all mean?.
Includes bibliographical references (p. 172-191) and index.
Professional
Keywords: Effective teaching; Teacher effectiveness; Teachers; Teaching